A PILOT STUDY ON DIABETIC PATIENTS AT MALANG COMMUNITY HEALTH CENTER REGARDING THE APPLICATION OF THE T-PLATE MODEL CONCEPT - Dwipajati (Universitas Airlangga, 2023)
Introduction: Diabetes mellitus is a comorbidity that is often found in Covid-19 patients with a 3.9-fold risk of death. Data from the Malang City Health Office shows an increase in the number of diabetes patients by 1.2% each year. In Indonesia, 3J (right amount, type, and eating time) has become the principle of diabetes diet therapy, but in practice, it is still challenging to apply independently. Aims: Investigating the T-Plate Model as a simple eating guide for people with diabetes mellitus. Methods: This pilot study included 18 diabetic patients at some Primary Health Care who were 50–70 years old and had a BMI more than 23 kg/m2. The participant was split into two groups, with nine people in the (C) group eating according to the T-Plate Model, and others in the (T) group eating according to the T-Plate Model after eating fruit. After a 3-month treatment period, BMI, blood pressure, carbohydrate, and fiber consumption were assessed. Mean BMI and blood pressure were examined using paired sample t-tests (p 0.05). Results: Both groups' BMIs fell into the category of obesity level 1 before to treatment periods: C group (26.09+3.13 kg/m2) and T group (27.15+ 4.15). We discovered significant blood pressure and BMI variations in the T group at the end of intervention periods (p 0.05). Nevertheless, systolic blood pressure was different in the C group (p 0.05). Conclusions: It may be inferred that using the T-Plate Model with the addition of fruit initially can lower blood pressure and BMI.